Theoretical aspects to consider for the generation of a non formal participative model of environmental education orientated towards the protection and conservation of the wetlands Bañó and Los Negros, Colombia - Villadiego-Lorduy, Jorge (2013)
The existing environmental problems in the wetlands of Bañó and Los Negros are the result of the anthropic pressures to which they have been submitted; in the absence of cultural environmental ones, their inhabitants have spoilt present day ecosystems. In response to this, one of the four instruments of environmental management is applied, environmental education; understood as a systemic process that, based on the reflexive and critical knowledge of biophysical, social, political, economic and cultural realities, allows the individual to understand relationships of interdependence with his or her environment. Considering the previously mentioned above, a debate of theoretical aspects that could be included at the moment of proposing a non formal participative model of environmental education is intended, in order to respond to a series of basic questions that bring theoretical contributions to mind such as andralogical education, constructivist and significant learning, systemic interdisciplinary approaches, interpretive communities, the incorporation of values and environmental attitudes, and action–participation methodologies such as a participative survey. In the same way, the population, object of study, is integrated by adult persons whose ages range from 20 to 55 years and who possess a series of previous knowledge of their environment. As a conclusion, the development of a territorial diagnosis that allows for a true valuation of the area of study is considered a priority which will make it possible to identify the factors that are influencing environmental deterioration, and therefore also determine the pedagogic basis and central elements needed for the generation of a pedagogic environmental model.